In-Ovo Antiviral Activity of Hibiscus sabdariffa against Newcastle Disease Virus - Abaka, AbdulAzeez Mumsiri; Hamuel, James Doughari; Abdullahi, Tukur Baba; Abubakar, Keta Biman (Biology, Medicine, & Natural Product Chemistry, 2024)
Newcastle disease is a highly contagious viral infection affecting poultry and wild birds. The causative agent is Avian paramyxovirus 1 (APMV-1), causing significant economic losses despite vaccination efforts due to its high mortality rate. Hibiscus sabdariffa was identified at Modibbo Adama University Yola, and laboratory assays were performed at the National Veterinary Research Institute Vom. The study explores the antiviral effects of extracts from H. sabdariffa calyx against a virulent strain of Newcastle Disease Virus (NDV) using embryonated chicken eggs (ECE). Standard methods were employed for cytotoxicity assay, embryo infective dose 50 (EID50) determination, and therapeutic antiviral assays. Methanol was used for extraction and phytochemical analysis, revealing various bioactive compounds like cardiac glycosides, alkaloids, flavonoids, terpenes, and phenols. Toxicity assay showed cytotoxicity at concentrations over 25 mg/ml, but therapeutic antiviral assays demonstrated virus replication inhibition at concentrations as low as 5 mg/ml. These findings suggest the potential of H. sabdariffa calyx extracts as safe and effective treatments for NDV, with promising therapeutic antiviral properties. Further pharmaceutical research is recommended to explore their use in developing novel Newcastle Disease treatments.